Effects of Financial Inclusion on the Economic Growth of Developing Countries: An Empirical Analysis of the Bangladesh Economy - Noor, Md Asad; Hossain, Tanjela; Shirazi, Hasan (South Asian Journal of Social Sciences and Humanities, 2022)
Financial inclusion in its widest meaning refers to inexpensive access to an extensive variety of financial facilities. These include banking products, insurance, stock investments, and other financial services. Financial inclusion helps economic development by widening the financial system’s resource base and encouraging rural residents to save. It also helps the rural economy grow. In this study, from 2011 to 2020, the connection between financial inclusion and economic development is examined. Financial inclusion is assessed by the number of Automated Teller Machines (ATMs) and the credit-deposit ratio (CDR), among other factors. Multiple regression analysis was used to analyze secondary data, along with other approaches. Before analysis, the data were checked for completeness and correctness. VIF and Durbin-Watson tests examined multicollinearity and autocorrelation in the data. The study’s policy implications include that financial inclusion, in all of its forms, is determined to be one of the most important components of economic development. The study focuses that the government and other policymakers must strive to preserve and promote sustainable and inclusive growth, which may be achieved via the expansion of financial inclusion. Furthermore, the results provide support to the government of Bangladesh’s social banking initiatives, which are being carried out in order to promote financial inclusion. The research found that ATMs significantly boost the country’s GDP. Nonetheless, the CDR has a little beneficial influence on the GDP.